The Coumarin-Derivative Esculetin Protects against Lipotoxicity in Primary Rat Hepatocytes via Attenuating JNK-Mediated Oxidative Stress and Attenuates Free Fatty Acid-Induced Lipid Accumulation - Mengmeng Xia; Zongmei Wu; Junyu Wang; Manon Buist-Homan; Han Moshage (MDPI AG, 2023)
Coumarin derivates have been proposed as a potential treatment for metabolic-dysfunction-associated fatty liver disease (MAFLD). However, the mechanisms underlying their beneficial effects remain unclear. In the present study, we explored the potential of the coumarin derivate esculetin in MAFLD, focusing on hepatocyte lipotoxicity and lipid accumulation. Primary cultures of rat hepatocytes were exposed to palmitic acid (PA) and palmitic acid plus oleic acid (OA/PA) as models of lipotoxicity and lipid accumulation, respectively. Esculetin significantly reduced oxidative stress in PA-treated hepatocytes, as shown by decreased total reactive oxygen species (ROS) and mitochondrial superoxide production and elevated expression of antioxidant genes, including Nrf2 and Gpx1. In addition, esculetin protects against PA-induced necrosis. Esculetin also improved lipid metabolism in primary hepatocytes exposed to nonlipotoxic OA/PA by decreasing the expression of the lipogenesis-related gene Srebp1c and increasing the expression of the fatty acid β-oxidation-related gene Ppar-α. Moreover, esculetin attenuated lipid accumulation in OA/PA-treated hepatocytes. The protective effects of esculetin against lipotoxicity and lipid accumulation were shown to be dependent on the inhibition of JNK and the activation of AMPK, respectively. We conclude that esculetin is a promising compound to target lipotoxicity and lipid accumulation in the treatment of MAFLD.